Comparative Advantage of Indonesia with Competitive Countries For Exporting of World Spices - Anggrasari, Herdiana; Saputro, Wahyu Adhi (Universitas Sebelas Maret, 2021)
Exports are an important component in the economy. The higher the export performance, the greater the positive impact. Indonesia is one of the producers of spices and is included in the 5 largest spice producing countries in the world so that it has great opportunities and potential to be developed. This study aims to determine the comparison of Indonesia's comparative advantage with competing countries for world spice exports. This study uses the basic analytical descriptive method. The data used in this research is secondary data. Secondary data in this study include data on area area, production, productivity from FAO (fao.org) and data on exports and imports from UN Comtrade (comtrade.un.org). Based on the results of the research, it can be seen that Indonesia is still in the top 4 position in the world spice commodity exporter. When viewed from the acreage and production of spices, Indonesia is still in the top rank, especially in the commodities of cinnamon, cloves and nutmeg. In the international market, it can be seen that the percentage of the market share for Indonesian spices is in fourth place.